Sita Marital Harta Bersama Dalam Perkara Perceraian di Pengadilan Agama - Gunawan, Edi; Hakim, Budi Rahmat; Bonok, Risdianti (Prodi Siyasah (Hukum Tata Negara) Fakultas Syari'ah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: The process of resolving marital seizure applications on joint assets in a divorce case at the Religious Court is carried out with stages starting from the application of the marital seizure to objects, both movable and immovable goods. It is highly dependent on concrete and demonstrable reasons regarding seizure placement in trial face. If the seizure request can be granted by the panel of judges according to strong evidence and proven in the trial, the panel of judges can conduct marital seizure by ordering the registrar to be assisted by the bailiff to confiscate movable or immovable items to be recorded. Marital seizure contained in the object of the dispute in the contents of the claim with the local government present. Whereas judicial legal considerations regarding marital seizure applications, the panel of judges, firstly looks at the facts from the trial. If the seizure is granted then enough reason for seizure applicants to be placed marital seizure. And if the seizure application is rejected and there is no enough reason to place the marital seizure by the panel of judges because there was no concern, the defendant will move or transfer the object of the dispute to another person who was carried out through a hearing outside the Religious Court which is also called the local hearing. Keywords: Marital Seizure, Joint Property, Case, Divorce Abstrak: Proses penyelesaian permohonan sita marital terhadap harta bersama dalam perkara perceraian di Pengadilan Agama dilakukan dengan tahapan-tahapan mulai dari permohonan peletakan sita marital terhadap objek, baik barang bergerak maupun tidak bergerak, sangat bergantung pada  alasan yang kongkrit dan dapat dibuktikan mengenai peletakan sita di muka persidangan, apabila  permohonan sita dapat dikabulkan oleh majelis hakim sesuai bukti yang kuat dan dibuktikan dalam persidangan maka majelis hakim dapat melakukan sita marital dengan memerintahkan Panitera yang dibantu oleh jurusita untuk melakukan sita baik barang bergerak atau tidak bergerak untuk dicatat, Selanjutnya panitera membuat berita acara sita marital yang terdapat dalam objek sengketa dalam isi gugatan dengan dihadirkan pemerintah setempat. Sedangkan pertimbangan hukum hakim mengenai permohonan sita marital, majelis hakim terlebih dahulu melihat pada fakta-fakta yang lahir dalam persidangan, apabila sita dikabulkan maka cukup alasannya bagi pemohon sita untuk diletakkan sita marital dan apabila permohonan sita ditolak maka tidak cukup alasan untuk diadakan peletakkan sita marital oleh majelis hakim karena tidak ditemukan kekhawatiran tergugat akan memindahkan atau mengalihkan objek sengketa kepada orang lain yang dilakukan melalui sidang di luar gedung Pengadilan Agama yang dinamakan dengan sidang pemeriksaan setempat. Kata Kunci: Sita Marital, Harta Bersama, Perkara, Perceraian